Design Options for a Strategic Reserve for the German Power Market and International Coordination - Karsten Neuhoff; Sebastian Schwenen (Deutsches Institut für Wirtschaftsforschung, 2014)
Strategic reserves are in principle well suited to address both generation adequacy and system security in power markets. Depending on the power system and on the network topology, a strategic reserve has to be designed to fulfill both objectives. For the design of a strategic reserve (SR) in the German context, this implies that the strategic reserve should be able to deal with local scarcities in the south arising from network constraints that threat system security, as well as to maintain generation adequacy at the system-wide level. This distinction will be of particular importance for a German strategic reserve that could either replace or run in parallel to the current `Netzreserve'. Policymakers also will have to decide on the degree to which additional policy goals such as strategies for coal-fired plants may be reflected in the overall power market design and hence also within a strategic reserve. International coordination for the design of any capacity remuneration mechanisms (CRMs) offers the potential of cost-reductions as the size of coordinated reserve capacities may decrease. If a reserve can deliver value and serve critical load in neighboring countries, coordinated CRMs, especially in central Europe should be further explored. At the same time, the role of interconnectors and the role of international re-dispatch after SR activation have to be taken into account. While technical factors have to be considered yet, many lessons for implementing a strategic reserve exist, as for example relying on experiences in Belgium, Sweden, Poland and Finland.
Keywords: L94; Q48; 330; German Power Market; Market Design